Identification of bacteria in endodontic infections by sequence analysis of 16S rDNA clone libraries - Saito, D.; Leonardo, RDT; Rodrigues, JLM; Tsai, S. M.; Hofling, J. F.; Goncalves, R. B. (Soc General Microbiology, 2006)
A significant proportion of oral bacteria are unable to undergo cultivation by existing techniques. In this regard, the microbiota from root canals still requires complementary characterization. The present study aimed at the identification of bacteria by sequence analysis of 16S rDNA clone libraries from seven endodontically infected teeth. Samples were collected from the root canals, subjected to the PCR with universal 16S rDNA primers, cloned and partially sequenced. Clones were clustered into groups of closely related sequences (phylotypes) and identification to the species level was performed by comparative analysis with the GenBank, EMBL and DDBJ databases, according to a 98 % minimum identity. All samples were positive for bacteria and the number of phylotypes detected per subject varied from two to 14. The majority of taxa (65(.)2 %) belonged to the phylum Firmicutes of the Gram-positive bacteria, followed by Proteobacteria (10(.)9 %), Spirochaetes (4(.)3 %), Bacteroidetes (6(.)5 %), Actinobacteria (2(.)2 %) and Deferribacteres (2(.)2 %). A total of 46 distinct taxonomic units was identified. Four clones with low similarity to sequences previously deposited in the databases were sequenced to nearly full extent and were classified taxonomically as novel representatives of the order Clostridiales, including a putative novel species of Mogibacterium. The identification of novel phylotypes associated with endodontic infections suggests that the endodontium may still harbour a relevant proportion of uncharacterized taxa.